Herbal alternatives for the treatment of hepatic disorders: An updated review - PASWAN, SHRAVAN KUMAR; Verma, Prittt; Raj, Abhisek; Rastogi, Chetan; Srivastava, Sajal; Rao, Ch V (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The liver is an amazingly complex organ which virtually affects every physiological process of the body. The liver is the largest glandular organ in body, and has more function than any other organs. Hepatic disorders which stem from a stressful life style, inappropriate eating habits and lack of exercise have become one of the major causes of morbidity and mortality in human being. The acute hepatic symptoms may be cured by some general prevention such as avoidance of constipation and balance between intake quantity of protein and disaccharides in normal food. An alternative and a progressively increasing adaptation is the use of herbal extracts. Many of the plant based drugs show effective response in managing the hepatotoxicity and secondary symptoms of liver damage. While, the models used for conventional hepatotoxicity evaluation are still outdated, in the present review we have attempted to provide updated information of the molecular pathogenesis and aspects for the role of herbalpharmacotherapy in alleviation of hepatic ailments. Furthermore, we have attempted to summarize the critical findings on hepatoprotective herbs over a period of last 20 year. In this article different hepatotoxicity pharmacological model such as carbon tetra chloride, paracetamol and thiocetamide induced are studied for different plants drugs. In summary this article contains the entire elucidated concept for hepatotoxicity including its causes, pathogenesis and treatment of liver disease.